Effect of rotational deformities after pediatric femoral fracture on clinical outcome - AKGÜLLE, AHMET HAMDİ; KESİMER, MEHMET DENİZ (My University, 2022)
Femoral shaft fractures are the most common pediatric injuries that require hospitalization. Early closed reduction and spica casting are one of the most popular treatment options. One of the significant complications of spica casting is rotational deformities of the fracture. The present study aimed to determine the potential effects of rotational deformities in pediatric patients who underwent early spica casting after a femoral shaft fracture. Pediatric patients who underwent early spica casting following femoral shaft fractures were screened retrospectively. Radiological measurements were made on the patients\" initial postop radiographs who could be measured rotationally according to the defined radiological method. Twenty-three patients with more than 10 degrees of rotation in their measurements were included in the study. Differences in leg length and rotation between both legs were calculated with clinical examination methods for all patients in the study. The gaits of the patients were observed; patient and family complaints were obtained. We found a strong and positive correlation between the rotational measurement made on the X-ray and the clinical measurement (R: 0.634, P: 0.001). For measurements made on X-ray, the mean rotational value was calculated as 27.2 +/- 6.9 degrees. After the patients\" clinical examination, an average of 3.0 +/- 1.7 degrees rotational difference was found between the broken limb and the healthy limb. No patient or family complained of trauma. Early spica casting, according to the age of the patient, is an effective treatment method. There may still be certain degrees of deformity after treatment, but patients well tolerate them even at high degrees. Accordingly, it was concluded that the rotational deformities less than 30 degrees would not cause clinical problems on children under 4 years of age which may require postoperative revisions or the use of various costly imaging techniques and include radiation.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Cerrahi Tıp Bilimleri; Ortopedi ve Travmatoloji; Medicine; Health Sciences; Internal Medicine Sciences; Child Health and Diseases; Surgery Medicine Sciences; Orthopedics and Traumatology; ORTOPEDİ; Klinik Tıp; Klinik Tıp (MED); PEDİATRİ; ORTHOPEDICS; CLINICAL MEDICINE; Clinical Medicine (MED); PEDIATRICS; Pediatrics; Orthopedics and Sports Medicine; Podiatry; Pediatrics, Perinatology and Child Health; early spica cast; femoral shaft fracture; fracture rotation; rotational deformity; SHAFT FRACTURES; CHILDREN; FEMUR